Anterior Segment Optical Coherence Tomography Evaluation of a Dexamethasone Intravitreal Implant in the Crystalline Lens: A Case Report - Santos-Oliveira J; Teixeira-Martins R; Ferreira AM; Macedo JP; Oliveira-Ferreira C (International Medical Case Reports Journal)
Joana Santos-Oliveira,1 Rita Teixeira-Martins,1 Ana Margarida Ferreira,1 João Paulo Macedo,1 Cláudia Oliveira-Ferreira1,2 1Department of Ophthalmology, Centro Hospitalar Universitário de São João, Porto, Portugal; 2Department of Surgery and Physiology, Faculty of Medicine, University of Porto, Porto, PortugalCorrespondence: Joana Santos-Oliveira, Department of Ophthalmology, Centro Hospitalar Universitário de São João, Alameda Prof. Hernâni Monteiro, Porto, 4200-319, Portugal, Email joana.santos.oliveira@ulssjoao.min-saude.ptPurpose: Ozurdex® is a dexamethasone intravitreal implant approved for the treatment of macular edema secondary to branch or central retinal vein occlusion, non-infectious uveitis affecting the posterior segment of the eye, and diabetic macular edema.Patients and Methods: We report a case of an accidental injection of the implant into the crystalline lens, successfully managed by surgery afterwards. The case description is supported by Anterior Segment Optical Coherence Tomography (AS-OCT) images.Results: A 69-year-old male was observed for bilateral diabetic macular edema. He had previously been treated with bevacizumab and aflibercept, with an incomplete anatomical response (< 20% reduction in central macular thickness). The patient consented to undergo a bilateral intravitreal dexamethasone injection (dexamethasone intravitreal implant (0.7 mg)). The procedures were uneventful, except for an extensive conjunctival hemorrhage in the right eye. An appointment was scheduled for fifteen days later, however the patient missed it. Four months later, he referred OD vision loss, which occurred a few days after the injection, and the implant was found within the right crystalline lens. An AS-OCT was done to better understand the implant’s location and entry point. Due to decreased visual acuity, the patient was scheduled for surgery. A phacoemulsification surgery with a three-piece hydrophobic intraocular lens implantation in the sulcus associated with anterior vitrectomy was done.Conclusion: The injection of a dexamethasone implant is becoming increasingly common. Nonetheless, it must always be carried out carefully, to avoid complications. If the implant is accidentally injected into the crystalline lens, the AS-OCT can help determine its exact location, which is important for preparing the surgical plan and determining the appropriate timing.Keywords: crystalline, intravitreal injections, lens, macular edema